Fuzzy AHP – DEMATEL Methods To Investigate Passengers’ Decision Factors On Using Public City Bus In An Indonesian Region - V. Reza Bayu Kurniawan; Trisna Yulianti; Fransiska Hernina Puspitasari (OPSI, 2021)
An advanced public transportation system becomes an indicator for a country. Accordingly, it is essential that the decision-makers (DMs) conduct an initial study based on passengers’ view in order to improve the public transportation services. Since involving multi factors, the problem is often solved using the multi-criteria decision-making (MCDM) approaches. This study aims to examine significant factors on passengers decision making to use public transportation using Fuzzy AHP and DEMATEL. The Fuzzy AHP method is proposed to determine criteria weights so that significant critera are obtained, then the causal relations including the criteria are visualized using DEMATEL. This study demonstrates the integration of the two MCDM methods in a BRT system in the region of Yogyakarta, Indonesia, and invites passengers and the DMs. The result indicated that 21 criteria are identified, while the 11 significant criteria are selected based on the Fuzzy AHP weight – α-cut screening. Besides, the DEMATEL has succeeded in describing the influence relationship for the criteria, where firstly, the significant criteria are classified into cause and effect group and secondly, the two criteria, namely coverage to strategic points and on time arrival, should be put on the top priority list. This study enables the DMs to solve public transportation problems more effectively. However, the follow-up study should be carried out by including other factors such as economic and sustainability to strengthen the decision-making process.